Uji Stabilitas Pooled Sera Yang Disimpan Di Suhu 2 - 8ºc Pada Pemeriksaan Albumin: The Pooled Sera Stability Test is Stored at a Temperature of 2 - 8ºc on Albumin - Ramdhani, Fitria Hariati; Purbayanti, Dwi; Astuti, Putri (Borneo Journal of Medical Laboratory Technology, 2023)
The health laboratory is one of the health services for the community in helping to establish a diagnosis, monitoring treatment results, and determining the prognosis of a disease. Control serum is very important for assessing performance in the laboratory, including instrument and reagent quality. Some laboratories use pooled serum as control serum for daily examination. Albumin is the most abundant plasma protein in the human body, which is about 55-60% and the total normal serum protein level is 3.8-5.0%. This study aims to test the stability of pooled sera on examination of albumin stored in the refrigerator at a temperature of 2 - 8ºC for 2 weeks. This research method uses observational research methods with precision data analysis techniques (accuracy). The results of the study of examining albumin levels using the Bromcresol Green (BCG) method obtained serum stability results on day 1 to day 5, where the CV value from the albumin level examination entered the maximum CV value on albumin, which was 6. The CV value for the 5th day covers, day 1 to day 2 = 1.99. Day 1 to day 3 = 2.17. Day 1 to day 4 = 4.27. And day 1 to day 5 = 4.84. On day 6 to day 14 and so on, the serum is found to be unstable and the value does not enter the maximum CV value.